A green synthetic route to the highly efficient K2SiF6:Mn4+ narrow-band red phosphor for warm white light-emitting diodes. Issue 11 (7th March 2018) - Hou, Ziyang; Tang, Xueyuan; Luo, Xuefang; Zhou, Tianliang; Zhang, Lin; Xie, Rong-Jun
Abstract : A green synthetic route to the highly efficient K2 SiF6 :Mn 4+ narrow-band red phosphor for warm white light-emitting diodes. Abstract : Mn 4+ -Doped K2 SiF6 (KSF:Mn 4+ ) is identified as a promising down-conversion narrow-band red phosphor used in warm-white light emitting diodes (wLEDs) or wide color gamut LED backlights, owing to its outstanding photoluminescence properties. However, the highly toxic and concentrated HF is essentially used as a raw material to synthesize KSF:Mn 4+ phosphors, which leads to environmental and safety issues. Herein, we report a novel green synthetic route to prepare highly efficient KSF:Mn 4+ red phosphors using non-toxic NH4 F/HCl instead of HF. The microstructure, photoluminescence properties and reaction mechanisms of the title phosphor were investigated and discussed. The KSF:Mn 4+ phosphor (4.8% Mn) synthesized by this green route exhibits a spherical particle morphology and a fine particle size of 5.5 μm. The internal and external quantum efficiencies of the phosphor are 92 and 44% under 460 nm excitation, respectively. A warm wLED using KSF:Mn 4+, YAG:Ce 3+ and a blue LED chip is demonstrated to have a luminous efficacy of 137.2 lm W −1, a correlated color temperature of 3585 K and a color rendering index of Ra = 88.1, respectively. This indicates that the proposed green synthetic approach enables the preparation of highly efficient KSF:Mn 4+ phosphors that have a comparable ability with the commercial ones to produce warm wLEDs.